IMPLEMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN MATERI ROLL DEPAN DALAM SENAM LANTAI PADA SISWA KELAS IV SD NEGERI PERESAK BEBUAK - Ahmad Rozali; Fadli Zainuddin; Susi Yundarwati (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The problems in this research are learning models that are less varied, learning which is still dominated by teachers, lack of interaction between students and lack of activity of students in participating in learning. IV SDN Peresak Bebuak. This classroom action research consisted of 2 cycles, in each cycle consisting of four stages, namely: planning, action implementation, evaluation and reflection. the research instrument in this classroom action research was in the form of process and outcome assessment instruments, process assessment used observation sheets of student and teacher activities, assessment of learning outcomes used student learning outcomes tests. The results showed that the percentage of students' learning activities in the first cycle was 37.04% with 10 students completing. Whereas in cycle II, the learning outcomes were 92.59% with the number of students who completed as many as 25 students out of 27 students in class IV SDN Peresak Bebuak. From these data, the results obtained are that the research conducted using the Discovery Learning learning model was considered successful with a satisfactory score and passed the KKM score of 70.